Financial analysis of Company XYZ - DiMattina, Ashleigh (Kansas State University, 2023)
Company XYZ is a small business, established in October 2021, that services a variety of vehicles for repairs and modifications. The current business model has reached its maximum workload output given shop space constraints. The objective of this study is to see how well Company XYZ is tracking or meeting company goals. Utilizing financial statements, invoices, and social media marketing, this study provides insight into the company’s future success and growth. An interview with the owner of Company XYZ provided information about future goals for the business, as well as relevant background information about their experiences in the automotive aftermarket industry. By completing a ratio analysis for Company XYZ from its start in October 2021 through December 2022, the study captured a broad view of the financial health and past success of Company XYZ. Completing another analysis of January and February 2023 numbers, provided information on the annual trend line used to inform future decisions. The comparison of Company XYZ’s numbers with industry numbers shows how well they perform against their competitors. The invoicing turnover rate (the number of days it takes an invoice to close) provided a clear picture of how the company is tracking towards their 2023 goal of 20 completed invoices each month with a minimum profit of $700 per invoice. Past profitability data showing where the company has been will help guide where the owners focus needs to fall for meeting future goals. Company XYZ uses social media marketing to reach its customer base and promote sales. Analyzing sales revenue resulting directly from one social media post. This provides a marketing model to facilitate the minimum number and type of social media marketing that will be needed to achieve company objectives. The two categories created for social media posts were family-related and job-related posts. Correlating the number of posts with total monthly sales provides insight into how significant social media marketing is in creating additional sales. Financial ratios indicated Company XYZ is financially healthy in comparison to the automotive repair industry. Invoices showed profitability for all but one out of 91 invoices. Social media posts overall drew in additional sales. When split into two categories, family-related posts had little impact on sales, while job related posts had a higher impact, although not statistically significant. Total posts overall compared to sales showed an even stronger impact on sales each month but was also not statistically significant. Additional factors play into what brings in monthly sales that were not discovered in this analysis.
Keywords: Financial analysis; Small business; Financial ratios; Social media analysis; Invoice analysis; Automotive aftermarket